Proceedings of SPE European Petroleum Conference 2000
DOI: 10.2523/65165-ms
|View full text |Cite
|
Sign up to set email alerts
|

SWAG Injection on the Siri Field - An Optimized Injection System for Less Cost

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractSimultaneous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…• Injectivity problems Owing to the low density of gas, the gas hydrostatic pressure at the bottom of the well is very small compared to that of any liquid. This implies reduced bottom hole pressures and its pressure differential with that of the formation, which ultimately affects the gas flow rate (Strom et al 1973;Quale et al 2000).…”
Section: North Sea Eor Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Injectivity problems Owing to the low density of gas, the gas hydrostatic pressure at the bottom of the well is very small compared to that of any liquid. This implies reduced bottom hole pressures and its pressure differential with that of the formation, which ultimately affects the gas flow rate (Strom et al 1973;Quale et al 2000).…”
Section: North Sea Eor Methodsmentioning
confidence: 99%
“…A more recent application is in the Siri field (see Table 5), and an increased oil recovery of 6% compared to a water injection scheme was reported. In the Siri field, during WAG injection, rapid segregation of gas to the top of the formation affected the microscopic sweep of the bottom oil (Quale et al 2000). This led to a change from WAG to SWAG in 1999.…”
Section: Simultaneous Water Alternating Gas (Swag) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of high-pressure immiscible CO 2 injection experiments that were performed in micromodel, Sohrabi and Emadi [17] showed that before breakthrough, the oil was displaced by a double-drainage mechanism which was boosted by CO 2 dissolution and viscosity reduction mechanism. They demonstrated that after the CO 2 breakthrough, the main contribution to oil recovery came from the extraction 0.68 nC 4 3.25 iC 5 2.75 nC 5 3.46 C 6 4.91 C 7 4.85 C 8 2.57 C 9 1.30 C 10 2.69 C 11 4 mechanism, in which CO 2 efficiently extracted and recovered part of the oil which was directly in contact with the CO 2 . Despite significant CO 2 dissolution and swelling of the trapped oil which was completely surrounded by water layers, reconnection and recovery of these isolated oil blobs took place in a very limited number of pores.…”
Section: Secondary Immiscible Swaco 2 Injectionmentioning
confidence: 99%
“…The pilot test results showed that the SWAG method improved the incremental recovery over waterflood and WAG by 11% and 4.5-5% original oil in place (OOIP), respectively (Ma et al, 1995). SWAG was also implemented in the Siri Field on the Danish continental shelf (North Sea) which showed more than 6% incremental oil recovery over waterflooding (Quale et al, 2000;Berge et al, 2002). Simultaneous water and CO 2 miscible flood in Joffre Viking Pool in Canada was the best CO 2 conformance compared to WAG and continuous gas injection (CGI) with incremental 282…”
Section: Introductionmentioning
confidence: 99%